Preparation method and application of composite aerogel material

By preparing agar/dialdehyde starch/NH2-MIL-101(Cr) composite aerogel, the problems of insufficient functional integration, poor environmental stability and limited regeneration capacity of existing composite aerogel materials were solved, realizing efficient adsorption and sensitive detection of nanoplastics, which is suitable for complex water quality environments.

CN120944177APending Publication Date: 2025-11-14GUANGXI UNIV FOR NATITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511063441.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing composite aerogel materials have shortcomings in terms of functional integration, environmental stability and regeneration capacity, making it difficult to efficiently capture and detect nanoplastics. Furthermore, traditional methods are costly and cumbersome to operate.

Method used

By preparing agar/dialdehyde starch/NH2-MIL-101(Cr) composite aerogel, a porous structure was formed using Schiff base reaction and freeze-drying techniques, and silver nanoparticles were loaded onto it, achieving efficient adsorption of nanoplastics and surface-enhanced Raman scattering detection.

Benefits of technology

It achieves integrated high-efficiency adsorption and in-situ detection of nanoplastics, with an adsorption capacity of 170.37 mg/g, a detection limit of 3.32 nm, low Cr3+ leaching, and is suitable for complex water quality environments. The material is recyclable and low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120944177A_ABST
    Figure CN120944177A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of environmental functional materials, in particular to a preparation method and application of a composite aerogel material.The preparation method comprises the steps that cassava starch and sodium periodate are mixed, pH is adjusted, stirring reaction is conducted for 5 hours, and freeze drying is conducted after centrifugal washing; the preparation method comprises the following steps: dispersing amino modified chromium ion metal organic framework 'NH2-MIL-101 (Cr)' powder in deionized water, adding dialdehyde starch, heating to 70 DEG C for gelatinization, then adding agar, and stirring; the sol is injected into a mold, retrogradation is conducted for 12 hours at the temperature of 4 DEG C, freezing and vacuum freeze drying are conducted for 48 hours, the composite aerogel is obtained, the prepared composite aerogel can efficiently adsorb polystyrene nano-plastic in water, dialdehyde starch in the aerogel serves as a cross-linking agent to enhance the stability of the material, silver nanoparticles can be reduced, and the stability of the material is improved. The maximum adsorption capacity to polystyrene nano plastic at 25 DEG C reaches 170.37 mg / g, and good regeneration performance and interference resistance are achieved. In addition, the leaching amount of chromium ions (Cr < 3 + >) is low, and the environmental protection standard is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmental functional materials technology, and in particular to a method for preparing and applying a composite aerogel material. Background Technology

[0002] In recent years, nanoplastics, as an emerging environmental pollutant, have been widely detected in water bodies, soil, and even organisms due to their small size, large specific surface area, and difficulty in degradation, attracting global attention. Nanoplastics mainly originate from the mechanical wear, photodegradation, or biodegradation processes of plastic products and can accumulate through the food chain, posing a potential threat to ecosystems and human health. However, current technologies for the treatment and detection of nanoplastics still face significant challenges: on the one hand, the high dispersibility, strong mobility, and interference from complex environmental matrices of nanoplastics make it difficult for traditional adsorption materials to capture them efficiently; on the other hand, existing detection methods generally suffer from insufficient sensitivity, cumbersome operation, or sample destruction, making it difficult to meet practical environmental monitoring needs. Currently, the removal of nanoplastics from water bodies mainly relies on adsorption, membrane separation, and chemical flocculation technologies. Among these, adsorption methods are widely studied due to their low cost and ease of operation, but traditional adsorbents such as activated carbon and clay minerals have limited affinity for nanoplastics, especially under the interference of complex water components (such as humic acid and salt ions), where adsorption efficiency significantly decreases. Furthermore, some nanomaterials (such as carbon-based materials) may release fragments due to structural instability, exacerbating the environmental burden.

[0003] Metal-organic frameworks (MOFs) are considered promising materials due to their high specific surface area, tunable pore size, and abundant surface functional groups. For example, amine-modified NH2-MIL-101(Cr) can enhance the capture of hydrophobic nanoplastics through electrostatic interactions and π-π stacking mechanisms. However, pure MOFs are prone to structural collapse, aggregation, or metal ion leaching in aquatic environments, leading to decreased adsorption performance and difficulty in recycling. Their single-function characteristics also limit their application in pollution control and detection. In the field of detection technology, surface-enhanced Raman scattering (SERS) has become a research hotspot due to its high sensitivity and non-destructive nature. However, the preparation of traditional SERS substrates (such as gold / silver nanoparticle arrays) is complex, costly, and has poor uniformity. Especially in complex water conditions, they are easily interfered with by organic matter or ions, leading to signal drift or increased background noise. Existing technologies usually require stepwise adsorption enrichment and SERS detection, which is cumbersome and may cause sample loss. Aerogels, as lightweight porous materials, have shown unique advantages in the field of pollutant adsorption due to their high porosity, tunable surface chemistry, and three-dimensional network structure. Natural polymer aerogels have attracted much attention due to their biocompatibility, low cost, and environmental friendliness. For example, agar can form a stable gel network through hydrogen bonding and physical cross-linking, while bisaldehyde starch can provide active aldehyde groups for functionalization after oxidative modification. Combining MOFs with aerogels can not only utilize the stable framework of aerogels to prevent MOF aggregation, but also enhance the mechanical strength and adsorption activity of the material through chemical bonding. However, existing composite aerogels still have problems such as insufficient functional integration, poor environmental stability, and limited regeneration capacity. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing composite aerogel materials and their applications, aiming to solve the problems of insufficient functional integration, poor environmental stability, and limited regeneration capacity of existing composite aerogels.

[0005] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a composite aerogel material, comprising the following steps:

[0006] Cassava starch and sodium periodate were mixed at a mass ratio of 1:1, the pH was adjusted to 3, the mixture was stirred and reacted for 5 hours, and then the mixture was centrifuged, washed and freeze-dried to obtain dialdehyde starch.

[0007] NH2-MIL-101(Cr) powder was dispersed in deionized water, the dialdehyde starch was added, and the mixture was heated to 70°C to gelatinize. Then agar was added and stirred to obtain a sol.

[0008] The sol was injected into a mold, refluxed at 4°C for 12 hours, frozen, and then freeze-dried under vacuum for 48 hours to obtain a composite aerogel.

[0009] The mass ratio of the NH2-MIL-101(Cr) powder, the dialdehyde starch, and the agar is 0.2g:0.15g:0.2g.

[0010] The composite aerogel has a hierarchical porous structure, containing C=N bonds and ether bonds generated by Schiff base reaction, and uniformly loaded with silver nanoparticles.

[0011] In a second aspect, the present invention also provides an application of a composite aerogel material, wherein the composite aerogel substrate prepared by the composite aerogel material preparation method described in the first aspect above includes the following steps:

[0012] The composite aerogel was immersed in a nanoplastic suspension and shaken for 1 hour to fully adsorb the nanoplastics.

[0013] The composite aerogel after adsorbing nanoplastics was heated and gelatinized, silver ammonia solution was added dropwise to reduce it to generate silver nanoparticles, and then dried to obtain ADNM@Ag thin film substrate.

[0014] 4-Mercaptobenzoic acid (4-MBA) was used as an internal standard to achieve quantitative detection of nanoplastics in the test solution via the internal standard method.

[0015] The amount of silver ammonia solution added was 100 μL, the reduction temperature was 70℃, and the adsorption capacity of the composite aerogel for polystyrene nanoplastics was 170.37 mg / g. Cr 3+ With a leaching amount of less than 6.8 μg / L, the composite aerogel is introduced into water containing nanoplastics. The nanoplastics are captured by a combination of porous adsorption, electrostatic interaction, π-π stacking, and hydrogen bonding. The particle size of the plastic ranges from 20 to 800 nm, the detection limit is 3.32 nm, and the signal stability RSD is ≤3.25% under conditions of humic acid ≤25 mg / L and common ion interference.

[0016] The ADNM@Ag thin film substrate is a surface-enhanced Raman spectroscopy substrate. The characteristic peaks of the nanoplastics are detected by Raman spectroscopy. The surface-enhanced Raman scattering detection uses a 532nm laser with an exposure time of 3 seconds and a power of 5%. The characteristic peaks of the CC skeleton vibration of polystyrene nanoplastics are detected, and the intensity is linearly positively correlated with the size of the nanoplastics.

[0017] This invention discloses a method for preparing a composite aerogel material. The method involves mixing cassava starch and sodium periodate at a mass ratio of 1:1, adjusting the pH to 3, stirring for 5 hours, centrifuging and washing, and then freeze-drying to obtain dialdehyde starch. NH2-MIL-101(Cr) powder is dispersed in deionized water, and the dialdehyde starch is added. The mixture is heated to 70°C for gelatinization, followed by the addition of agar and stirring to obtain a sol. The sol is then injected into a mold, regenerated at 4°C for 12 hours, frozen, and then freeze-dried under vacuum for 48 hours to obtain a composite aerogel. The composite aerogel prepared by this method has a framework structure of agar and dialdehyde starch. Freeze-drying technology was used to load NH2-MIL-101(Cr) metal-organic framework material, forming a three-dimensional network with high specific surface area and porous structure. This material can efficiently adsorb polystyrene nanoplastics in water, and rapid detection can be achieved through surface-enhanced Raman scattering (SERS). The dialdehyde starch in the aerogel not only acts as a cross-linking agent to enhance the stability of the material, but also reduces silver nanoparticles, further enhancing the SERS signal intensity. The composite aerogel achieved a maximum adsorption capacity of 170.37 mg / g for polystyrene nanoplastics at 25 °C, exhibiting good regeneration performance and anti-interference ability. Furthermore, its Cr... 3+ With low leaching levels, meeting environmental standards, it is suitable for the efficient removal and qualitative analysis of nanoplastics in complex aquatic environments, and has broad application prospects. It solves the problems of insufficient functional integration, poor environmental stability, and limited regeneration capacity found in existing composite aerogels.

[0018] The beneficial effects of this invention are as follows:

[0019] By constructing an agar (AG) / dextral starch (DS) / NH2-MIL-101(Cr) composite aerogel substrate (ADNM@Ag), efficient adsorption and in-situ detection of nanoplastics were integrated. Based on a three-dimensional porous network structure, this material exhibits excellent adsorption performance on polystyrene nanoplastics (PS NPs) through physical interception, electrostatic attraction, π-π stacking, and synergistic effects of hydrogen bonding. The maximum adsorption capacity reaches 170.37 mg / g at 25℃, and it maintains a removal efficiency of over 85% even in humic acid, high ionic strength, and complex water qualities. Simultaneously, the Schiff base reaction stabilizes the loaded NH2-MIL-101(Cr), effectively inhibiting metal ion leaching and meeting drinking water hygiene standards. In terms of detection, the dual aldehyde function of the dextral starch enables the in-situ generation of uniformly distributed silver nanoparticles in the aerogel, forming a high-density SERS hotspot, achieving sensitive detection of PS NPs in the 20-800 nm range, with the characteristic CC framework vibration peak (1001 cm⁻¹) clearly visible. -1 Strength is linearly positively correlated with the size of nanoplastics (R0). 2=0.9557). Furthermore, the thermosensitive properties of the aerogel simplify the adsorption-detection process. Combined with ethanol regeneration technology, the material can be recycled more than four times while maintaining an adsorption efficiency of 90%, significantly reducing usage costs. This method utilizes natural polymers and green processes, avoiding toxic reagents. The material is biodegradable, and its design concept demonstrates high applicability in various water environments, including tap water, lake water, and river water, possessing both environmental value and commercial potential. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 These are scanning electron microscope (SEM) images of ADNM (AC) and ADNM-adsorbed PSNPs (DF) and transmission electron microscope (TEM) images of ADNM (GI).

[0022] Figure 2 (A) is a schematic diagram of the Fourier transform infrared (FTIR) spectra of AG, DS, MOF and ADNM, and (B) is a schematic diagram of the particle size distribution of MOF, where Wavenumber is the wavenumber, Transmittance is the transmittance, Size is the size and Percentage is the percentage.

[0023] Figure 3 This is a schematic diagram of SEM (AC) and TEM (DF) of ADNM@Ag.

[0024] Figure 4 (A) is a schematic diagram of the morphology of aerogels prepared according to AG and DS contents. (B) is a schematic diagram of the effect of AG and DS contents on the adsorption of polystyrene nanoparticles (PS NPs). (C) is a schematic diagram of the effect of ADNM on the adsorption performance of PS NPs at different pH values. (D) is a schematic diagram of the effect of humic acid (HA) on the adsorption effect of ADNM. (E) is a schematic diagram of the effect of different ions on the adsorption performance of PSNPs. (F) is a schematic diagram of the ADNM recycling experiment, where Quantity is the number, Removal efficiency is the removal efficiency, pH is the acid-base value, HA is humic acid, and Number is the number.

[0025] Figure 5These are schematic diagrams of (A) the adsorption kinetics experiment of ADNM and (B) the pseudo-first-order kinetic model and pseudo-second-order kinetic model of the ADNM adsorption experiment.

[0026] Figure 6 This is the adsorption isotherm plot of ADNM, where Langmuir is the solid line and Freundlich is the dashed line.

[0027] Figure 7 This is a schematic diagram illustrating the impact of complex water quality on adsorption performance.

[0028] Figure 8 This is a schematic diagram of the uniformity (A, B) of MOF in ADNM, where Raman Shift is the Raman shift, Intensity is the intensity, and Counts is the count.

[0029] Figure 9 This is a schematic diagram of the SERS spectrum (A) and calibration curve (B) of PS NPs of different sizes.

[0030] Figure 10 This is a schematic diagram of the SERS performance of ADNM on PS NPs: repeatability (A), stability (B), and reproducibility (C).

[0031] Figure 11 This is a schematic diagram illustrating the effect of different ions in water on the SERS of PS NPs.

[0032] Figure 12 The SERS spectra (A) and 1001 cm⁻¹ spectra of PS NPs after adsorption in different aquatic environments are shown. -1 The intensity histogram (B).

[0033] Figure 13 These are the SERS spectra (A) of 4-MBA at different concentrations and at 1078 cm⁻¹. -1 The calibration curve at (B); the relative intensity I of the SERS spectra of PSNPs solutions of different concentrations (C). R A schematic diagram of PS concentration (D).

[0034] Figure 14 This is a flowchart of a method for preparing a composite aerogel material provided by the present invention.

[0035] Figure 15 This is a flowchart of a method for applying composite aerogel materials provided by the present invention. Detailed Implementation

[0036] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0037] Please see Figure 14 In a first aspect, the present invention provides a method for preparing a composite aerogel material, comprising the following steps:

[0038] S01. Cassava starch and sodium periodate were mixed at a mass ratio of 1:1, the pH was adjusted to 3, the mixture was stirred and reacted for 5 hours, and after centrifugation and washing, it was freeze-dried to obtain dialdehyde starch.

[0039] In this embodiment of the invention, cassava starch and periodic acid were added to deionized water at a mass ratio of 1:1, the pH was adjusted to 3, and the mixture was stirred for 5 hours. After centrifugation to wash away excess sodium periodate, the mixture was freeze-dried to obtain dialdehyde starch (DS) powder. The successful synthesis of the dialdehyde starch was confirmed by Fourier transform infrared visible spectroscopy.

[0040] S02 disperses NH2-MIL-101(Cr) powder in deionized water, adds the dialdehyde starch, heats to 70°C to gelatinize, then adds agar and stirs to obtain a sol;

[0041] In this embodiment of the invention, the method for preparing NH2-MIL-101(Cr) powder includes weighing 1,4-phthalic acid (H2BDC) and chromium nitrate (Cr(NO3)3·9H2O), placing them in a 50 ml polytetrafluoroethylene-lined container, adding hydrogen fluoride (HF) and ultrapure water, and then pouring in 3-aminopropyltrimethoxysilane solvent. The mixture is then sonicated and subjected to a hydrothermal reaction at 217–231 °C for 7.92–8.4 hours. The sample is separated by centrifugation, followed by reflux heating with ethanol at 79–84 °C for 5 hours. After cooling, it is centrifuged again and refluxed with ammonium fluoride solution at 59–63 °C. Finally, it is washed five times with ultrapure water at 59–63 °C to remove the ammonium fluoride. After drying the dark green sample at -33.25 to -35.35°C for 47.5 to 50.5 hours, it was ground with an agate mortar to obtain NH2-MIL-101(Cr) powder.

[0042] Add 0.2 DS and react at 70°C for 1 hour to link DS and NH2-MIL-101(Cr). The reaction type is a Schiff base reaction, specifically a reaction between aldehyde and amino groups. Add agar (AG) and react at 70°C for 1 hour to crosslink DS and AG to form a double crosslinked network. The crosslinking reaction consists of self-crosslinking between each molecule and acetal reaction between different molecules.

[0043] Both the cassava starch and the agar are polysaccharides that can self-crosslink into chain structures through intermolecular hydrogen bonds and van der Waals forces, making the materials green, environmentally friendly, and easily degradable. The successful loading of amino groups into the NH2-MIL-101(Cr) can be confirmed by Fourier transform infrared-visible spectroscopy.

[0044] S03 The sol is injected into a mold, refluxed at 4°C for 12 hours, frozen, and then freeze-dried under vacuum for 48 hours to obtain a composite aerogel.

[0045] In this embodiment of the invention, the sol is rapidly injected into a 12-well plate in a 3°C ice-water bath, and then placed in a refrigerator at 4°C to allow for DS regeneration. The regenerated ADNM is then freeze-dried to obtain ADNM aerogel (composite aerogel). The freeze-drying technique works by sublimating water molecules, causing the ice crystal structure to disappear after freezing, leaving the porous structure of the aerogel.

[0046] Please see Figures 1-15 Secondly, the present invention also provides an application of a composite aerogel material, wherein the composite aerogel substrate prepared by the composite aerogel material preparation method described in the first aspect above includes the following steps:

[0047] S11 The composite aerogel is immersed in a nanoplastic suspension and shaken for 1 hour to fully adsorb the nanoplastics.

[0048] In this embodiment of the invention, aerogel is introduced into water containing nanoplastics, and the nanoplastics are captured synergistically through porous adsorption, electrostatic interaction, π-π stacking, and hydrogen bonding. The nanoplastics have a particle size range of 20-800 nm, a detection limit of 3.32 nm, and are present in humic acid (≤25 mg / L) and common ions (Na+). + Ca 2- Cl - SO4 2- Signal stability under interference: RSD ≤ 3.25%.

[0049] S12 heats and gelatinizes the composite aerogel after adsorbing nanoplastics, adds silver ammonia solution to reduce it to generate silver nanoparticles, dries it, and obtains ADNM@Ag thin film substrate;

[0050] In this embodiment of the invention, after the composite aerogel adsorbs nanoplastics, it is heated at 70°C for 40 minutes, and then silver ammonia solution is added to reduce the silver nanoparticles. Subsequently, it is dried to obtain the SERS substrate (ADNM@Ag sheet substrate).

[0051] S13 uses 4-mercaptobenzoic acid as an internal standard to achieve quantitative detection of nanoplastics in the test solution through the internal standard method.

[0052] To better understand this technical solution, the following embodiments are provided for further explanation:

[0053] Example 1

[0054] A method for preparing MOF aerogel integrating adsorption and detection of nanoplastics includes the following steps:

[0055] (1) Using the oxidizing property of sodium periodate (NaIO4), 2,3-o-dihydroxyl groups on the cassava starch (CS) chain were selectively oxidized to synthesize dialdehyde starch (DS). CS and NaIO4 were mixed in a beaker at a mass ratio of 1:1. 200 mL of deionized water was added, and the pH was adjusted to 3. After stirring for 5 hours, DS was obtained. The obtained DS was centrifuged at 1000 rpm and repeatedly washed with deionized water to remove excess NaIO4. Finally, it was frozen in a refrigerator and then freeze-dried under vacuum to obtain DS powder.

[0056] (2) Weigh 1,4-phthalic acid (H2BDC) and chromium nitrate (Cr(NO3)3·9H2O), place them in a 50ml PTFE-lined container, add hydrogen fluoride (HF) and ultrapure water, and then pour in 3-aminopropyltrimethoxysilane solvent. The mixture is then sonicated and subjected to a hydrothermal reaction at 217–231℃ for 7.92–8.4 hours. The sample is separated by centrifugation, followed by reflux heating with ethanol at 79–84℃ for 5 hours. After cooling, it is centrifuged again and refluxed with ammonium fluoride solution at 59–63℃. Finally, it is washed five times with ultrapure water at 59–63℃ to remove ammonium fluoride. The dark green sample is dried at -33.25–35.35℃ for 47.5–50.5 hours and then ground with an agate mortar to obtain NH2-MIL-101(Cr) powder.

[0057] (3) Weigh 0.2 g of NH2-MIL-101(Cr) powder using an analytical balance and pour it into a 50 ml three-necked flask. Add 10 ml of deionized water and stir for 2 hours. Then weigh 0.15 g of the prepared DS powder and pour it into the three-necked flask. Place the flask in an oil bath with a magnetic stirrer at 70 °C and stir for 40 min to gelatinize the DS. Then add 0.2 g of agar and stir for 2 hours to completely crosslink the agar with the dialdehyde starch. Add 1 ml of the solution to a 24-well plate placed in an ice bath each time. Then place the 24-well plate in a 4 °C freezer for 12 hours to warm up, then freeze for 6 hours, and finally freeze-dry in a freeze dryer for 48 hours to finally prepare a flexible three-dimensional ADNM aerogel.

[0058] In addition, the applicant also conducted an applied study on the adsorption capacity of the obtained MOF aerogel material as follows:

[0059] First, a 100 mL standard solution was prepared from a 100 nm polystyrene nanoparticle (PS NPs) solution. This solution was then diluted sequentially to obtain 100 nm PS NPs solutions with concentrations of 0 mg / L, 5 mg / L, 10 mg / L, 15 mg / L, and 20 mg / L. Next, the quartz cuvette was cleaned twice with the prepared PS NPs standard solutions to ensure cleanliness. The prepared PS NPs standard solutions were then placed in a fluorescence spectrophotometer for detection. The fluorescence spectrophotometer was set to photometry, with a bandwidth of 5 nm, a photomultiplier tube (PMT) voltage of 700 V, a fixed excitation wavelength of 488 nm, and an emission wavelength of 518 nm. The fluorescence intensity of each standard solution was measured sequentially from lowest to highest concentration. Based on the measurement results, a standard curve was plotted between fluorescence intensity and PS NP concentration (e.g., ...). Figure 1 (As shown)

[0060] Next, the applicant investigated the effects of agar content and dialdehyde starch content on the adsorption experiment:

[0061] The adsorption performance of ADNM aerogel for PS NPs was evaluated by varying the contents of agar and dialdehyde starch. The Schiff base reaction between dialdehyde starch and NH2-MIL-101(Cr) effectively and uniformly immobilized it within the aerogel, directly affecting its formation and adsorption performance. The adsorption efficiency was significantly higher than 95% when the agar content was 0.05 parts and 0.2 g, with the optimal adsorption effect achieved at a 0.2 part content, resulting in a uniform surface pore distribution. The optimal dialdehyde starch content (0.15 parts) exhibited the best gel structure and adsorption performance. Therefore, an agar-to-starch mass ratio of 4:3 was selected for the synthesis of ADNM aerogel.

[0062] Subsequently, the applicant investigated the effect of pH value on the adsorption effect of nanoplastics:

[0063] The effect of different pH conditions on adsorption efficiency showed a trend of first increasing and then decreasing with increasing pH. When pH < 7, amino groups in the aerogel were protonated, but electrostatic attraction dominated adsorption. Excess H₂... + This leads to a decrease in hydrogen bond donor capacity, preventing the adsorption capacity from reaching its optimal level. At pH 7, the amino groups in the aerogel reach optimal protonation equilibrium, enhancing electrostatic attraction. Simultaneously, the presence of C=N bonds, ether bonds, and other structural elements in the aerogel strengthens the polar interactions, π-π interactions, and van der Waals forces of hydrogen bonds. Under the influence of these four forces, the adsorption effect reaches its peak. When pH > 7, the protonation of the amino groups in the aerogel makes them electrically neutral, resulting in electrostatic repulsion with negatively charged PS NPs. Furthermore, the presence of competing OH- ions affects hydrogen bonding, weakening the adsorption effect. Therefore, the adsorption effect is optimal at pH 7.

[0064] Furthermore, the applicant investigated the effects of humic acid and various ions on the adsorption effect:

[0065] At a humic acid concentration of 0 mg / L, the removal efficiency was close to 100%, but it decreased significantly as the concentration increased to 25 mg / L. ADNM aerogel contains ether bonds, C=N bonds, and amino groups, which can effectively adsorb PS NPs through electrostatic adsorption, hydrogen bonding, π-π interactions, and van der Waals forces. However, with increasing humic acid concentration, humic acid molecules compete with the functional groups in the aerogel for adsorption sites, leading to a decrease in the adsorption capacity for PS NPs. Therefore, its adsorption performance weakens with increasing humic acid concentration.

[0066] The cation contains Na. + Mg 2+ K + Ca 2+ The adsorption efficiency in this environment was slightly lower than that under ion-free conditions, indicating that these four ions may competitively bind with C=N bonds, amino groups, and ether bonds in the material, thus weakening the adsorption of PS NPs. Since the impact was relatively small, it suggests that the material possesses a strong PS NP capture capacity in this environment. However, NH4+ is present in the water. + At that time, due to NH4 + Hydrolysis reaction produces H + This acidification of the solution alters the pore structure of the ADNM aerogel and weakens the polar interactions of hydrogen bonds, thus affecting the adsorption effect. In an anionic environment, Cl - , The overall adsorption efficiency in the environment is relatively high, but... There is a significant reduction in the environment, mainly due to Hydrolysis reaction occurs in the solution to produce OH- - This creates a weakly alkaline environment in the solution, reducing electrostatic adsorption. The adsorption sites in the aerogel compete with each other, thus inhibiting the binding with PS NPs. Therefore, this result indicates that the aerogel material is suitable for the removal of nanoplastics in most aquatic environments.

[0067] Furthermore, the applicant investigated the adsorption and regeneration effects of ADNM:

[0068] To comprehensively evaluate the practical application capability of ADNM aerogel, an adsorption-regeneration cycle experiment was conducted. The aerogel after adsorbing PSNPs was rinsed three times with anhydrous ethanol, then immersed in anhydrous ethanol and sonicated for 1 minute, and then dried in a 60°C oven. The regenerated ADNM aerogel was then subjected to repeated adsorption. Figure 7 The figure shows the removal efficiency of ADNM for PSNPs during the cycling process. As can be seen from the figure, the adsorption efficiency is close to 100% during the first cycle, indicating a significant synergistic effect of the ether bonds, C=N bonds, and amino functional groups of the aerogel. Amino groups capture PSNPs through static interactions, while ether and C=N bonds provide high specific surface area and a stable structure. Simultaneously, functional groups provide hydrogen bonding, π-π interactions, and van der Waals forces, enhancing the adsorption capacity. However, the removal rate gradually decreases with increasing cycle number. After four cycles, the removal rate remains above 90%, but after five cycles, the adsorption efficiency declines. This is because repeated use leads to a decrease in the specific surface area due to aerogel pore collapse, partial detachment of adsorption sites of amino and other functional groups during regeneration, and hydrolysis of C=N bonds, weakening the adsorption activity. However, the decrease remains within 10% after four cycles and is still above 90%. These results highlight the potential feasibility of ADNM aerogel in environmental applications.

[0069] Furthermore, the applicant conducted adsorption kinetics and thermodynamic studies:

[0070] To further evaluate the adsorption performance of ADNM aerogel for PS NPs, adsorption kinetics experiments were conducted. Data showed that the adsorption capacity of ADNM for PS NPs exhibited a time-dependent increasing trend. With continuous extension of reaction time, the adsorption performance gradually improved, indicating a positive correlation between adsorption and time. After 60 minutes, the adsorption capacity plateaued. Because ADNM aerogel contains a large number of adsorption sites, short adsorption times resulted in the adsorption of some microplastics, but the adsorption sites were not yet saturated. The plateauing of adsorption capacity after 60 minutes indicates that the adsorption sites had reached saturation. To better understand and evaluate the adsorption process, pseudo-first-order and pseudo-second-order kinetic models were analyzed. Figure 1 It can be seen that in the quasi-first-order model, R 2 The value is 0.9217, indicating that the model can describe the adsorption process well. In the pseudo-second-order kinetic model, R... 2 The value is 0.9678, and the R-squared value of the quasi-second-order dynamics model is... 2 The higher kinetics than the pseudo-first-order model indicate that the model better matches the experimental data. Therefore, the adsorption process of PS NPs by ADNM aerogel is more consistent with the pseudo-second-order kinetic model, and this adsorption process may be controlled by a chemisorption mechanism.

[0071] Table 1

[0072]

[0073] The adsorption performance of ADNM aerogel for PS NPs was evaluated by testing temperature. Since the aerogel's AG (aggregate ions) dissolves and breaks its structure at higher temperatures, experiments were conducted at 25℃, 35℃, and 45℃. PS NPs were adsorbed at different temperatures, and Langmuir and Freundlich models were fitted to determine the relationship between temperature and adsorption efficiency. The adsorption isotherms show that the adsorption capacity gradually increases with increasing equilibrium concentration, eventually approaching equilibrium. Table 2 shows that in the Langmuir model, the maximum adsorption capacity is 170.368 mg / g. With increasing temperature, the maximum adsorption capacity gradually decreases, and KL also decreases with increasing temperature, indicating a weakening adsorption strength. In the Freundlich model, KF and n also decrease with increasing temperature, but their R... 2 The value is slightly lower than that of the Langmuir model, therefore the Langmuir model is more consistent with its adsorption process, indicating that the adsorption process is monolayer adsorption. Chapter 2 explains that the NH2-MIL-101(Cr) material undergoes an endothermic reaction, with adsorption efficiency increasing with increasing temperature. However, this aerogel material exhibits a decrease in adsorption efficiency with increasing temperature. This is because the aerogel is affected by its swelling rate; as temperature increases, the aerogel swells more, as shown in Table 3. With increasing temperature, the water absorption capacity of AG and DS increases, causing expansion and pore blockage, preventing PS NPs from entering the aerogel and thus reducing the adsorption effect.

[0074] Table 2

[0075]

[0076] Table 3

[0077]

[0078] Furthermore, the applicant investigated the application of this material in complex environments, and found that ADNM aerogel can still effectively remove PS NPs in complex water conditions.

[0079] Furthermore, the applicant studied the chromium ion leaching amount of the material, such as... Figure 4 Cr 3+ The leaching amount is lower than the requirements of the "Standards for Drinking Water Quality" and meets the standards.

[0080]

[0081] Furthermore, the applicant conducted an optimized evaluation of the SERS performance of the material:

[0082] I. Evaluation of SERS signal uniformity of ADNM aerogel

[0083] To evaluate the uniformity of MOFs in the aerogel of ADNM, NH2-MIL-101(Cr) was used as a marker, and 20 points were randomly selected on the surface of the ADNM aerogel for SERS testing. The SERS values ​​were taken at 1601 cm⁻¹. -1 The Raman peak generated by the contraction vibration of the benzene ring was used as the judgment object. The relative standard deviation (RSD) was 6.06%, and the relatively uniform SERS signal indicated that the MOF was uniformly distributed in the aerogel.

[0084] II. Research on SERS detection of nanoplastics of different sizes

[0085] We investigated the qualitative detection capability of ADNM aerogel for PS NPs. First, we measured the activity of PS NPs of different sizes (20 nm, 100 nm, 300 nm, 500 nm, 800 nm) at a depth of 1001 cm⁻¹. -1 The observation of distinct characteristic peaks of PS NPs at 1001 cm⁻¹ indicates that the PS NPs have been successfully adsorbed into the ADNM aerogel, mainly due to vibrations of the PS CC backbone. Furthermore, the PS NPs exhibited characteristic peaks at 1001 cm⁻¹. -1 The SERS intensity at 1001 cm⁻¹ significantly increased with increasing PS NP size. A linear relationship between SERS intensity and PS NPs of different sizes was established at 1001 cm⁻¹, showing a strong linear and positive correlation. The fitted equation was y = 31.67x + 4384, with a correlation coefficient R² of 0.9557. Furthermore, this equation yielded a detection limit (LOD) as low as 3.32 nm for ADNM substrates with PS NPs ranging from 20 to 800 nm. In conclusion, the size-dependent signal provides a reliable basis for the qualitative analysis of nanoplastics and is applicable to the qualitative analysis of nanoplastics of different sizes in environmental samples.

[0086] III. Study on the stability, repeatability, and reproducibility of ADNM

[0087] Using NH2-MIL-101(Cr) as a marker, the differences in SERS intensity at different sampling locations on the same substrate were compared. SERS intensity measurements at 100 nm PS NPs, taken at 10 randomly selected points on the substrate, showed relatively uniformity. The characteristic peak was observed at 1601 cm⁻¹. -1 The relative standard deviation (RSD) of the intensity at each point was 3.25%, indicating good repeatability of the substrate. The spectra of PS NPs were measured from five different batches of ADNM aerogel, with an RSD of 2.8%, demonstrating good reproducibility of the substrate. PS NPs were used to compare the SERS performance of the same batch of ADNM aerogel at different times, with measurements taken every 30 days. The characteristic peak of PS NPs was observed at 1001 cm⁻¹. -1The strength did not change significantly, indicating that the substrate's stability is also quite good. In conclusion, ADNM aerogel exhibits good SERS performance and can be used for the detection of nanoplastics.

[0088] IV. Internal Standard Method for Determining Nanoplastic Concentration

[0089] The Raman signal intensity of the nanoplastic PS varies with particle size. To conduct a quantitative study of PS, we used 4-MBA as an internal standard for SERS detection. The characteristic peak of 4-MBA is at 1078 cm⁻¹. -1 At this location, due to the stretching vibrations of CS, the SERS signal increases with increasing concentration. Different concentrations of 4-MBA at 1078 cm⁻¹... -1 The SERS intensity at the location shows a linear relationship, indicating a strong positive linear correlation between the two. The fitted equation is y = 109.8x + 1735, and R0... 2 =0.9786.

[0090]

[0091] I SERS and I RS This indicates the SERS intensity measured using a SERS substrate and non-SERS methods. N RS and N SERS This refers to the number of molecules in the bulk sample under laser irradiation and the number of molecules used in the analytical method of this study. The LOD value obtained by this equation is 0.83 mg / L, and the EF value is 1.57 × 10⁻⁶. 5 In summary, 4-MBA can be used to determine the internal standard peak for PS NP concentration.

[0092] A 200 mg / L PS NPs standard solution was diluted to (100, 50, 10, 5 mg / L) and measured. As the PSNPs solution concentration decreased, 1001 cm⁻¹... -1 The peak intensity also decreased accordingly. To obtain a linear quantification range, within the concentration range of 5 to 200 mg / L, it can be seen that as the concentration of PS NPs increases, the internal standard peak (1078 cm⁻¹) decreases. -1 The peak intensity of PS will decrease, but its trend is relatively gentle, so the competitive adsorption relationship between PS NPs and the internal standard is relatively weak. The relative intensity relationship between PS and 4-MBA is shown in formula (2):

[0093]

[0094] I 1001 Represents PS NPs at 1001cm -1 The characteristic peak intensity at I1078 This means that 4-MBA is at 1078cm. -1 The characteristic peak intensity at [location]. Within the concentration range of 5-200 mg / mL, I […]. R It showed a good linear relationship with PS concentration, with a linear correlation coefficient R. 2 =0.951, and the linear regression equation is y = 0.5618x - 0.0765, where y is the ratio intensity of I1001 / I1078, and x is the concentration of PS NPs. The detection limit (LOD) for PS NPs is 4.50 mg / L.

[0095] The above description is merely a preferred embodiment of the preparation method and application of a composite aerogel material of the present invention. It should not be construed as limiting the scope of the present invention. Those skilled in the art can understand that all or part of the processes of the above embodiments can be implemented, and equivalent changes made in accordance with the claims of the present invention are still within the scope of the invention.

Claims

1. A method for preparing a composite aerogel material, characterized in that, Includes the following steps: Cassava starch and sodium periodate were mixed at a mass ratio of 1:1, the pH was adjusted to 3, the mixture was stirred and reacted for 5 hours, and then the mixture was centrifuged, washed and freeze-dried to obtain dialdehyde starch. NH2-MIL-101(Cr) powder was dispersed in deionized water, the dialdehyde starch was added, and the mixture was heated to 70°C to gelatinize. Then agar was added and stirred to obtain a sol. The sol was injected into a mold, refluxed at 4°C for 12 hours, frozen, and then freeze-dried under vacuum for 48 hours to obtain a composite aerogel.

2. The method for preparing the composite aerogel material as described in claim 1, characterized in that... ; The mass ratio of the NH2-MIL-101(Cr) powder, the dialdehyde starch, and the agar is 0.2g:0.15g:0.2g.

3. The method for preparing the composite aerogel material as described in claim 1, characterized in that... ; The composite aerogel has a hierarchical porous structure containing C=N bonds and ether bonds generated by the Schiff base reaction, and is uniformly loaded with silver nanoparticles.

4. An application of a composite aerogel material, comprising a composite aerogel substrate prepared using the composite aerogel material preparation method according to any one of claims 1-3, characterized in that, Includes the following steps: The composite aerogel was immersed in a nanoplastic suspension and shaken for 1 hour to fully adsorb the nanoplastics. The composite aerogel after adsorbing nanoplastics was heated and gelatinized, silver ammonia solution was added dropwise to reduce it to generate silver nanoparticles, and then dried to obtain an agar dialdehyde starch double crosslinked amino modified chromium ion metal-organic framework composite aerogel (ADNM@Ag) sheet substrate loaded with silver nanoparticles. Using 4-mercaptobenzoic acid as an internal standard, the quantitative detection of nanoplastics in the test solution was achieved through the internal standard method.

5. The method for preparing the composite aerogel material as described in claim 4, characterized in that... ; The amount of silver ammonia solution added was 100 μL, the reduction temperature was 70℃, and the adsorption capacity of the composite aerogel for polystyrene nanoplastics was 170.37 mg / g. Cr 3+ With a leaching amount of less than 6.8 μg / L, the composite aerogel is introduced into water containing nanoplastics. The nanoplastics are captured by a combination of porous adsorption, electrostatic interaction, π-π stacking, and hydrogen bonding. The particle size of the plastic ranges from 20 to 800 nm, the detection limit is 3.32 nm, and the signal stability RSD is ≤3.25% under conditions of humic acid ≤25 mg / L and common ion interference.

6. The method for preparing the composite aerogel material as described in claim 4, Its characteristics are: The ADNM@Ag thin film substrate is a surface-enhanced Raman spectroscopy substrate. The characteristic peaks of the nanoplastics are detected by Raman spectroscopy. The surface-enhanced Raman scattering detection uses a 532nm laser with an exposure time of 3 seconds and a power of 5%. The characteristic peaks of the CC skeleton vibration of polystyrene nanoplastics are detected, and the intensity is linearly positively correlated with the size of the nanoplastics.